Integrating Artificial Intelligence to Foster Soft Skills: Innovations for Sustainable Education in Higher Learning Institutions - Yehezkiel S. Palar (Tecno Scientifica Publisher, 2026)
The rapid advancement of Artificial Intelligence (AI) presents transformative opportunities for education, particularly in developing students' competencies for the future workforce. This research investigates the influence of AI integration in education on the enhancement of students' soft skills, with a specific focus on communication skills. Employing a mixed-method approach, the study combines quantitative data from 100 student questionnaires with qualitative insights from focus-group discussions, framed by the Technology Acceptance Model (TAM) and Social Learning Theory (SLT). The findings indicate that students primarily recognize AI's potential in the cognitive and affective domains of learning, appreciating its utility for information access and personalized experiences. However, its impact on behavioral response, particularly the sustained development of communication-related soft skills, remains limited and unclear. While AI stimulates new, efficient study habits, it has not yet demonstrated the capacity to nurture the long-term, interactive practice essential for complex soft skill development. This study concludes that for AI to contribute meaningfully to sustainable education, its design and implementation must evolve beyond efficiency tools to include structured, social, and practice-oriented applications that actively foster critical interpersonal skills.